Kemampuan Menulis Ditinjau dari Struktur dan Bahasa Teks Prosedur Siswa Kelas VII - Angel Sri Angeli Lubis; Alber Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
In class VII SMPN 14 Kota Dumai, writing procedure texts is taught in odd semesters. Writing procedure text is very important for the development of students' imagination. Students are expected to develop their unique imagination and passion through written texts. In accordance with KD 4.6, provide procedural text with information about a series of activities (such as how to play musical instruments, regional dances, make souvenirs, etc.) taking into account the contents of the writing, linguistic elements, and structure. This research is included in the category of descriptive-quantitative research. The sample used in this study were 30 class VII students of SMPN 14 Dumai City. The ability to write procedural texts seen from the structure of the text is in the good category, while the ability to write procedural texts in terms of language rules is in the adequate category with an average of 75. This is in accordance with the findings and discussion of research on the ability to write procedural texts for class VII students of SMP Negeri 14 Kota Dumai 2022/2023 Academic Year.